1992
DOI: 10.1017/s0022215100120006
|View full text |Cite
|
Sign up to set email alerts
|

Combined internal maxillary and anterior ethmoidal arterial occlusion: the treatment of choice in intractable epistaxis

Abstract: Whilst it is generally accepted that the standard management for anterior or benign epistaxis is either cautery or anterior nasal packing, that of posterior or intractable epistaxis remains controversial. Various modalities of treatment, ranging from posterior nasal packing to arterial ligation and embolization, have been advocated but none have been unanimously accepted as the treatment of choice.The purpose of this paper was to determine the efficacy of internal maxillary arterial ligation versus combined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…1 Involvement of the ethmoid arterial systems in refractory epistaxis should also be considered after nasal injury, anterior skull base trauma, or recent endoscopic sinus surgery. 11 Previous studies evaluated the presence of supernumerary ethmoid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Involvement of the ethmoid arterial systems in refractory epistaxis should also be considered after nasal injury, anterior skull base trauma, or recent endoscopic sinus surgery. 11 Previous studies evaluated the presence of supernumerary ethmoid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…1 A few years before, Singh and Snyderman had found that ligature of the sphenopalatine artery associated with ligature of the anterior ethmoidal artery reduced the number of recurrences, and therefore the need for additional anesthesia and surgery to control bleeding. 5,6 Ligature of the anterior ethmoidal artery is classically described using the external approach. Common complications are scarring, facial edema, and damage to the medial canthal ligament, which may affect drainage in lacrimal ducts and result in epiphore.…”
Section: Discussionmentioning
confidence: 99%
“…39,42,45,47 However, we have only 3 patients with meningioma who were treated with this technique. It is therefore difficult to quantitate the efficacy of our procedure, as there are no external or internal controls.…”
Section: 44mentioning
confidence: 99%